The drumming signals of three winter stonefly species (Capniidae, Leuctridae: Plecoptera); with discussion resolving two common interval patterns - Sandberg, John B. (Illiesia, 2015)
The drumming signals of three winter stonefly species from two intermittent California Coast Range streams are described. Calileuctra dobryi male calls have monophasic and decreasing varied beat-interval patterns. Mesocapnia frisoni calls have monophasic and increasing varied beat-interval patterns. Calileuctra ephemera calls only have decreasing varied beat-interval patterns. There is considerable overlap in the mean interbeat intervals of the two allopatric Calileuctra species and only slight differences in mean number of beats/call and call duration. However, the mean interbeat interval pattern provides the most accurate recognition of the species. From a review of 34 Nearctic descriptive drumming papers (1977 to 2011), the term diphasic was inconsistently used to describe percussive signals in two different ways: the interbeat interval pattern (radically changing rhythm) and the signal pattern (two repeated calls composed of differing beat counts and interbeat intervals). Currently, the term monophasic is used to describe nearly-even or unchanging signal interval patterns. The definitions of 20 drumming variables are provided and four broad descriptive characters are updated, including a generalized example of three interbeat interval patterns with analyses and pattern determinations. The accuracy and precision of three sound analysis programs are compared, and methods for drumming signal recording, digital signal analysis, and experimental research are presented.
Keywords: entomology; stoneflies; Mesocapnia; Plecoptera; seismic communication; vibrational communication; Calileuctra; drumming